Fearless innovation : going beyond the buzzword to continuously drive growth, improve the bottom line, and enact change - Goryachev, Alex, 1975- (John Wiley & Sons, Inc., 2020)
"The pace of disruption only seems to be accelerating. For companies large and small, startups and multinational giants like Cisco, employees must find a way to innovate their companies and stay ahead of the competition. As the head of Innovation Strategy and Programs at Cisco, Alex Goryachev believes that workers can't wait for innovation to come from the top down -- it has to happen at every level of an organization. In Embracing Innovation, Goryachev distills his years of experience as well as examples from across industries to create a roadmap for innovation and survival in the 21st Century. Chapters include 'Organize Your Grassroots Co-Conspirators, ' 'Identify Revolutionary Outcomes, ' 'Arm Innovators for Success, ' and 'Constantly Evolve the Revolution.' Goryachev takes readers through every stage of innovation from motivating for change, identifying problems (internal and external) and opportunities, winning approval, effecting change, and keeping momentum"--